Freedom as a basis for the value of law - Глинянська, О. В. (Theory and practice of jurisprudence, 2016)
The article is devoted to the definition of the legal nature of freedom, it guarantees. Freedom is considered as the principle of the rule of law. Analyzes the consolidation of freedom in the constitutions of different countries.